1997
DOI: 10.1094/mpmi.1997.10.2.247
|View full text |Cite
|
Sign up to set email alerts
|

Expression of avrPphB, an Avirulence Gene from Pseudomonas syringae pv. phaseolicola, and the Delivery of Signals Causing the Hypersensitive Reaction in Bean

Abstract: Protein production encoded by the avirulence gene avrPphB from Pseudomonas syringae pv. phaseolicola was examined. Incorporation of [35S]-labeled methionine into the AvrPphB protein indicated processing of the full-length peptide in Escherichia coli to give a major 28-kDa product. The 28-kDa native peptide was isolated from E. coli following over-expression of avrPphB and found not to elicit the hypersensitive response (HR) after infiltration into bean leaves. Antiserum raised to the 28-kDa peptide allowed exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 45 publications
3
53
0
1
Order By: Relevance
“…Despite some inconsistencies, these data shown that the loss of pathogenicity and HR phenotypes of the rpoN mutant is most easily explained by the failure to activate hrp and avr transcription in the rpoN mutant. In general, our data are consistent with previously proposed models of hrp regulation in P. syringae in which HrpS plus RpoN ( 54 ) activate hrpL and in which HrpL activates avr genes and the remaining genes in the hrp cluster (63,80,81). To further test this model, we placed hrpL expression under control of the E. coli lacZ promoter.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite some inconsistencies, these data shown that the loss of pathogenicity and HR phenotypes of the rpoN mutant is most easily explained by the failure to activate hrp and avr transcription in the rpoN mutant. In general, our data are consistent with previously proposed models of hrp regulation in P. syringae in which HrpS plus RpoN ( 54 ) activate hrpL and in which HrpL activates avr genes and the remaining genes in the hrp cluster (63,80,81). To further test this model, we placed hrpL expression under control of the E. coli lacZ promoter.…”
Section: Discussionsupporting
confidence: 90%
“…A conserved sequence, GGAACCNA-N14-CCAC NNA, which appears to be responsible for hrpL-dependent transcription, has been identified upstream of a variety of avr genes (81). In several cases, including avrRpt2 and avrRpm1, hrpL dependence has been confirmed experimentally (34,35,46,63,66,70,81). Thus, the loss of hrp by mutation of a putative hrp regulator such as rpoN should affect HR induction by blocking avr gene transcription and type III-mediated protein delivery.…”
mentioning
confidence: 98%
“…As expected, the cytoplasmic DnaK protein was almost exclusively detected in the soluble fraction. Similar results were obtained with E. coli MC4100 harboring the complete P. syringae phaseolicola TTS regulon on the low copy number cosmid pPPY430 and the hrpL factor under lac control on a separate plasmid (23,38). MC4100/ pPPY430/pHrpL grown in the presence (Fig.…”
Section: Resultssupporting
confidence: 83%
“…In the absence of a corresponding R gene product, the avr product enhances virulence; however, in hosts which have the corresponding R gene, recognition of the avr gene product enhances host resistance. Interestingly, most avr genes are also coordinately regulated with genes in the hrp cluster (27,29,46,67,71,77,97).The HR is accompanied by the induction of defense-related genes (7, 91) that are differentially expressed depending on the particular pair of avr and R gene products eliciting the HR (70, 72). Defense gene induction also occurs in the absence of the HR during compatible pathogen-host interactions, although usually later and at lower levels than those occurring during an HR (11,32,66).…”
mentioning
confidence: 99%
“…In the absence of a corresponding R gene product, the avr product enhances virulence; however, in hosts which have the corresponding R gene, recognition of the avr gene product enhances host resistance. Interestingly, most avr genes are also coordinately regulated with genes in the hrp cluster (27,29,46,67,71,77,97).…”
mentioning
confidence: 99%